The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10704-007-9114-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of loading rate on dynamic fracture initiation toughness of brittle materials

Abstract: Numerical simulation is carried out to investigate the effect of loading rate on dynamic fracture initiation toughness including the crack-tip constraint. Finite element analyses are performed for a single edge cracked plate whose crack surface is subjected to uniform pressure with various loading rate. The first three terms in the Williams' asymptotic series solution is utilized to characterize the crack-tip stress field under dynamic loads. The coefficient of the third term in Williams' solution, A 3 , was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Thus, the observed increase in crack initiation toughness is attributed to the time required to reach a critical stress state ahead of the crack tip over a critical distance. The similar investigations on the effect of loading rate were conducted by Kalthoff (1986) who predicted the existence of an incubation time for crack initiation and by Kim and Chao (2007) who proposed a crack-tip constraint model. Liu et al (1998) analytically modelled the experimental measurements of Ravi-Chandar and Knauss (1984a) for Homalite-100 material by estimating the critical SIF on the basis of different critical distance δ.…”
Section: Dynamic Crack Initiation Toughnessmentioning
confidence: 76%
“…Thus, the observed increase in crack initiation toughness is attributed to the time required to reach a critical stress state ahead of the crack tip over a critical distance. The similar investigations on the effect of loading rate were conducted by Kalthoff (1986) who predicted the existence of an incubation time for crack initiation and by Kim and Chao (2007) who proposed a crack-tip constraint model. Liu et al (1998) analytically modelled the experimental measurements of Ravi-Chandar and Knauss (1984a) for Homalite-100 material by estimating the critical SIF on the basis of different critical distance δ.…”
Section: Dynamic Crack Initiation Toughnessmentioning
confidence: 76%
“…Both Belenky et al [17] and Kim and Chao [19] reported significant increases in fracture toughness at increased loading rates for monolithic ceramics.…”
Section: High Rate Testsmentioning
confidence: 99%
“…Fracture behavior of brittle material with innate flaws has attracted much attention recently. Extensive researches on crack initiation, propagation and coalescence have been conducted by using the specimens containing single flaw or multiple flaws in either artificial materials or real rocks under static loads, 1-6 impact loads [7][8][9][10][11][12][13][14][15][16] or blasting loads. 17 Classical fracture mechanics has gone so far as to answer a large number of questions about fracture behavior under various kinds of loads, but for the issue of a running crack approaching a pre-existing crack, there still remain a multitude of unanswered or partially unanswered aspects, such as how the pre-existing crack would affect the running crack?…”
Section: Introductionmentioning
confidence: 99%